Clinico-microbiological aspects of tinea corporis in North India: emergence of Trichophyton tonsurans - Kaur, Isampreet; Chaudhary, Anuradha; Singh, Harshvardhan (International Journal of Research in Dermatology, 2019)
Background: Tinea corporis is a superficial fungal infection of the glabrous skin of the trunk and extremities caused by closely related organisms of the three genera of dermatophytes– Trichophyton, Microsporum and Epidermophyton. The prevalence of the different species varies according to geographic and climatic regions. This study was an attempt to find out the causative fungal agents in clinically suspected cases of tinea corporis. Methods: During a period of six months from June 2017 to November 2017, various skin samples from clinically suspected cases of dermatophytosis were examined for presence of fungal elements using KOH preparation and culture on Sabouraud’s dextrose agar. The causative organisms were identified using conventional methods. Results: A total of 157 skin samples were obtained and processed. The most common age group involved was 21 to 30 years of age with male to female ratio of 1.5:1. The patients of rural area (67%) predominated over urban (33%) with most of the patients presenting in the monsoon season (43%). The KOH positivity was seen in 51% and culture positivity in 50% of samples. The dermatophytes (62.9%) predominate over non-dermatophytes (37.1%) with Trichophyton tonsurans isolated as the commonest causative fungal agent. Conclusions: Due to the great variation in the presence of fungal species in different places and at different times, mycological examination is necessary to diagnose, differentiate and treat dermatophytosis.